2010
DOI: 10.4049/jimmunol.0903681
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Noncytotoxic and IL-10–Producing CD8+AT2R+ T Cell Population in Response to Ischemic Heart Injury

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 21 publications
7
70
1
2
Order By: Relevance
“…During the last couple of years, our group demonstrated that ischemic, sterile myocardial injuries can elicit lymphocyte activation directed against cardiac antigens (13)(14)(15)(16). Our previous data, showing for the first time that CD4 + T cells reactive to cardiac components can foster the healing process that takes place after myocardial infarction, were corroborated by several other reports (13,15,(17)(18)(19)(20). However, these autoreactive T cells can also be potentially deleterious (21).…”
supporting
confidence: 75%
“…During the last couple of years, our group demonstrated that ischemic, sterile myocardial injuries can elicit lymphocyte activation directed against cardiac antigens (13)(14)(15)(16). Our previous data, showing for the first time that CD4 + T cells reactive to cardiac components can foster the healing process that takes place after myocardial infarction, were corroborated by several other reports (13,15,(17)(18)(19)(20). However, these autoreactive T cells can also be potentially deleterious (21).…”
supporting
confidence: 75%
“…In canine and mouse models of experimental infarction, IL-10 mRNA and protein expression is markedly upregulated, exhibiting a prolonged time course of expression (81,117). Subpopulations of T cells and macrophages are the cellular source of IL-10 in infarcted myocardial segments (69,117). In the canine model, IL-10 induction in the infarct is associated with attenuated expression of proinflammatory cytokines (117).…”
Section: Soluble Mediators As Negative Regulators Of the Postinfarctimentioning
confidence: 98%
“…A subset of CD8 + T-cells that express angiotensin 2 receptor has been observed in the peri-infarct zone of rats 7 days after MI. 55 These CD8 + T-cells differ from cytotoxic angiotensin 2 receptor-negative CD8 + T-cells in their capacity to secrete IL-10 in response to angiotensin-II stimulation in vitro. Transferring these cells, harvested from a donor rat 7 days after MI, reduced infarct size 2 weeks after MI, thereby indicating CD8 + T-cells' potential significance in myocardial wound healing.…”
Section: T-cell Subsets Other Than Cd4 + T-cellsmentioning
confidence: 99%